PENGARUH MEDIA SOSIAL TERHADAP TINDAK PIDANA CABUL YANG DILAKUKAN OLEH ANAK DI KOTA PADANG - Rozsa Rezky Febrian (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Sexual violence against children by children set on Article 76D and 76E of LawNo. 35 of 2014 Amending Law on Child Protection (No. 23/2002). Thedevelopment of social media has positive and negative effects. The negative effectschange culture, morality, and society value in general and increase number ofcrime by children specially. From the research results obtain several conclusions:First, the effects of social media on sexual violence against children by children inPadang City is about 82 percent. Through social media, children can accesspornography easily by facebook, whatsapp, twitter, instagram and etc. Somecases happen after children watching video by link in the social media. Second,Padang Police Resort’s effort to solve sexual violence against children bychildren cases caused by social media through three steps: preemptive, preventiveand repressive. The preemptive step is the first step by police to prevent a crime.The preventive step is special activities to eradicate the factors of violation bychildren, such as pornography access. The last, the repressive step handling byCrime Investigation Unit to investigate until deliver the case sheaf to prosecutor.